Fall risk assessment in elderly with and without history of falls: relationship between disorders of balance, fear of falling and gait changes: a comparative study - Coutinho, António (2014)
Objectives: The aim of this study was to assess the changes that occur in the balance, fear of falling and kinematic parameters such as stride length, velocity and time support in elderly with and without a history of falling. Main objective was also to verify whether a relationship exists between changes in gait parameters evaluated, balance and fear of falling. Methods: The sample comprised 30 patients (15 with history of falls and 15 without a history of falls), which met the criteria for inclusion and exclusion. The kinematic evaluation was performed in the dominant leg, which was right in this sample. The stride length, speed and duration of support were assessed using the program Kinovea and for assessment of balance and fear of falling were assessed using the Berg Balance Scale and the Falls Efficacy Scale. Statistical analysis was performed with SPSS version 20. Results: There were no significant differences in the parameters analyzed, except for scores on the Berg Balance Scale (p=0.000) between groups with and without history of falls. However, there is a decrease in the length of the stride and duration of left leg support and the increased length of right leg support, the speed and the fear of falling. The relationship between the parameters obtained, there is only statistically significant result between speed and stride length (r=0.507, p=0.004) and between the score of the Berg Balance Scale and the stride length (r=0.393, p=0,032). Conclusion: Although not having obtained statistically significant results we can conclude that in elderly with a history of falls have changes in speed and stride length that can be related to balance disorders and the aging process itself. However, it is concluded that the use of the Berg Balance Scale is more responsive and effective in the detection of changes occurring in the individual after a fall, and subsequent evaluation of the risk of falling that performing a kinematic analysis.